Effects of long-term litter manipulation on soil carbon, nitrogen, and phosphorus in a temperate deciduous forest. (April 2015) - Huang, Wenjuan; Spohn, Marie
Abstract: Changes in above-ground litterfall can influence below-ground biogeochemical processes in forests. In order to examine how above-ground litter inputs affect soil carbon (C), nitrogen (N) and phosphorus (P) in a temperate deciduous forest, we studied a 14-year-old small-scale litter manipulation experiment that included control, litter exclusion, and doubled litter addition at a mature Fagus sylvatica L. site. Total organic C (TOC), total N (TN) and total P (TP), total organic P (TOP), bioavailable inorganic P (Pi), microbial C, N and P, soil respiration and fine root biomass were analyzed in the A and in two B horizons. Our results showed that litter manipulation had no significant effect on TOC in the mineral soil. Litter addition increased the bioavailable Pi in the A horizon but had no significant effect on N in the mineral soil. Litter exclusion decreased TN and TP in the B horizon to a depth of 10 cm. In the A horizon of the litter exclusion treatment, TP, TOP and bioavailable Pi were increased, which is most likely due to the higher root biomass in this treatment. The high fine root biomass seems to have counteracted the effects of the excluded aboveground litter. In conclusion, our study indicates that aboveground litter is not an important source for C in the mineral soil and that P recycling from root litter might be more important than from above-ground litter. Highlights: Litter manipulation had no influence on soil total carbon in the mineral soil. Litter exclusion increased total P, organic P and bioavailable P in the A horizon. Litter exclusion increased fine root biomass in the A horizon. Litter exclusion deceased total N and P in the B horizon. P recycling from root litter might be more important than from leaf litter.